John Chrysostom and the mission to the Goths: Rhetorical and ethical perspectives - De Wet, Chris L. (HTS teologiese studies, 2012)
This study examines the role of John Chrysostom as bishop-missionary to the Goths in Constantinople. After Theodosius declared Nicene orthodoxy to be the only valid and legal faith, a potent programme to establish orthodoxy in Constantinople had begun, with bishops like Gregory Nazianzen and Nectarius promoting the cause. During and shortly after Chrysostom’s arrival in Constantinople, most of the Arians were Goths, and Chrysostom became personally involved in their affairs. In the light of this, the study specifically looks at how Chrysostom constructs and negotiates barbarian identity, with special emphasis on the rhetorical and ethical dimensions of his involvement; with emphasis on the trajectories provided by Foucault and De Certeau for understanding rhetoric, ethics and identity. It is specially asked whether Chrysostom could escape the classical Graeco-Roman habitus of barbarism and the normativity of the free, male Roman body.